Cardiac allograft vasculopathy following fecal microbiota transplantation for recurrent C. difficile infection. Issue 6 (19th September 2018) - Barfuss, Spencer; Knackstedt, Elizabeth Doby; Jensen, Kyle; Molina, Kimberly; Lal, Ashwin
Abstract: We report the case of a 3‐year‐old male who developed recurrent Clostridium difficile infection after receiving an orthotopic heart transplant. Despite multiple courses of antibiotics, C. difficile infection was persistent and he underwent a fecal microbiota transplant. The patient responded with resolution of his diarrhea. However, within 2 months he developed severe mixed rejection with high circulating donor‐specific antibodies and significant coronary vasculopathy. Organ dysfunction led to the need for re‐transplantation. The patient's postoperative course has since been complicated by pneumatosis intestinalis and recurrent C. difficile infection.